Acceleration of Handling Out-of-School Children (OOSC) in Pandeglang District - Ombi Romli (Universitas Syiah Kuala, 2023)
Pandeglang Regency is one of the regencies in Banten Province that has a high number of out-of-school children (OOSC). Therefore, to alleviate out-of-school children, it is necessary to accelerate the handling of OOSC in Pandeglang Regency. The purpose of this research is to study the factors that cause OOSC, constraints, and ways to handle OOSC in Pandeglang Regency. The data was obtained through interviews, observations, document studies and FGDs. The results showed that the factors that cause children not to go to school are the mindset of the child's parents, the economic weakness of the child's family, the child's access to school is far or difficult, early marriage of children, bullying at school. As a way to accelerate the handling of out-of-school children in Pandeglang Regency by working (collaboration) with the community.